IoT technologiesfor smart cities. Issue 1 (1st January 2018) - Hammi, Badis; Khatoun, Rida; Zeadally, Sherali; Fayad, Achraf; Khoukhi, Lyes
Abstract : The large deployment of Internet of things (IoT) is actually enabling smart city projects and initiatives all over the world. Objects used in daily life are being equipped with electronic devices and protocol suites in order to make them interconnected and connected to the Internet. According to a recent Gartner study, 50 billion connected objects will be deployed in smart cities by 2020. These connected objects will make the authors' cities smart. However, they will also open up risks and privacy issues. As various smart city initiatives and projects have been launched in recent years, theyhave witnessed not only the expected benefits, but the risks introduced. They describe the current and future trends of smart city and IoT. They also discuss the interaction between smart cities and IoT and explain some of the drivers behind the evolution and development of IoT and smart city. Finally, they discuss some of the IoT weaknesses and how they can be addressed when used for smart cities.